XIX in MMI in HISK : Laureaten 2001 - Bogaert, Wina; Doove, Edith; Elias, Willem; Mellaerts, Betty; Pas, Johan; Ruiz, José Maria; Ruyters, Marc; Schildermans, Ingrid; Snyders, Frank; Swinnen, Johan; Tegelaers, Theo (Antwerpen : HISK (Hoger Instituut voor Schone Kunsten), 2001)
Aertsen, Gert ; Bogaert, Wina ; Claeyé, Catherine ; Coolen, Caroline ; Denys, Ward ; Dockx, Nico ; Jessen, Joseph ; Maes, Ives ; Naveau, Nadia ; Paelinck, Lieven ; Redjaian, Haleh ; Renneboog, Lucie ; Ruiz, José Maria ; Sosnowski, Marika ; Tosseyn, Tom ; van Haren Noman, Ruth ; Vermeersch, Pieter ; Visic, Loreta ; Volders, Jethro
Nederlands & Engels
XIX in MMI in HISK / XIX at HISK in MMI, HISK (Hoger Instituut voor Schone Kunsten) Antwerpen,opening: vrijdag 1 juni 2001, open: 2, 8, 9, 15, 16 juni 2001
boek